Вивчення сортової стійкості троянди садової гібридної (Rosa × hybrida hort.) до грибних захворювань у відкритому ґрунті Донецького ботанічного саду Нан України - Bondarenko-Borisova, I.V.; Peltikhina, R.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2008)
The article presents results on phythopathology study of 58 varieties of Rosa × hybrida hort. in the open area of the Donetsk Botanical Gardens. Variety resistance to the most deleterious in the region fungus diseases – powdery mildew, blackspot, and rust was assessed. Indices of disease extention and intensity are given as well as an average affection of varieties. High resistance to fungus diseases was shown by 27 varieties and this allowes to recommend them for wide use in city and home landscaping of south-east of Ukraine. 6 varieties with high incidence of disease are recommended for limited use in city landscaping.